PENINGKATAN KUALITAS PEMBELAJARAN DI MADRASAH TSANAWIYAH: PENGARUH MANAJEMEN SEKOLAH DAN BUDAYA MUTU - Airohaniah Airohaniah; Zamroni Zamroni; Mohammad Salehudin (STKIP PGRI Situbondo, 2023)
The purpose of this study was to determine the effect of school management and quality culture on improving the quality of learning in the Madrasah Tsanawiyah City of Balikpapan, the instruments were compiled theoretically with clear indicators and had been tested for validity and reliability, totaling 64 instruments, while the number of respondents was 62 people who gave answers and returned them. , while the collection of answers through WAG and Google Forms were distributed to all Madrasah Tsanawiyah teachers in Balikpapan City. The results of the study found that there were significant results and the acceptance of the research hypotheses X1 and X2 on Y, meaning that the management variables of education and quality culture on the quality of learning were accepted as significant, and had an effect of 85.0%. These two variables